2015
DOI: 10.1021/acs.nanolett.5b00315
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Control of Surface Immobilized BMP-2: Toward a Quantitative Assessment of BMP-Mediated Signaling Events

Abstract: In this work we determine the impact of surface density of immobilized BMP-2 on intracellular signal transduction. We use block copolymer micellar nanolithography to fabricate substrates with precisely spaced and tunable gold nanoparticle arrays carrying single BMP-2 molecules. We found that the immobilized growth factor triggers prolonged and elevated Smad signaling pathway activation compared to the same amount of soluble protein. This approach is suitable for achieving controlled and sustained local deliver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
80
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(88 citation statements)
references
References 47 publications
8
80
0
Order By: Relevance
“…In this work we were able to show, that regardless of RGD and REDVfunctionalization, NP-distances of 90 nm were less favorable for EC and SMC cell adhesion than distances of 40. This finding is in supported by previously results [8,9,10,11], describing a critical ligand (RGD) density of approximately 67 nm. At larger NP-spacing, integrin adhesion can still take place, yet the adhesions formed fail to develop into stable structures.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this work we were able to show, that regardless of RGD and REDVfunctionalization, NP-distances of 90 nm were less favorable for EC and SMC cell adhesion than distances of 40. This finding is in supported by previously results [8,9,10,11], describing a critical ligand (RGD) density of approximately 67 nm. At larger NP-spacing, integrin adhesion can still take place, yet the adhesions formed fail to develop into stable structures.…”
Section: Discussionsupporting
confidence: 92%
“…Surfaces with ligand spacing larger than 73 nm failed to induce the formation of such structures [7,8]. Similar studies using AuNPs arrays functionalized with integrin-specific ligand revealed similar distance-dependencies [10] or demonstrated the ability of BMP2-functionalized AuNPs arrays to trigger elevated SMAD-signaling pathway activation [11]. In this work we were able to show, that regardless of RGD and REDVfunctionalization, NP-distances of 90 nm were less favorable for EC and SMC cell adhesion than distances of 40.…”
Section: Discussionmentioning
confidence: 74%
“…The co-operation of BMP 2 and Coll I signalling pathways has been reported in osteoblast differentiation previously [26,68]. The interaction of surface-immobilised BMP 2 with BMP receptor complexes on the cell surface leads to the initiation of intracellular signalling events without internalisation [69,70]. The BMP 2 signal is propagated through Smad 1 by phosphorylation of receptor-regulated Smad proteins 1/5/8, which then in turn bind to Smad 4 to induce osteogenic gene expression [31,71,72].…”
Section: Discussionmentioning
confidence: 94%
“…The proteins should be slowly released from the delivery systems in the former case. The latter immobilization systems have the advantage of controlled and sustained influence on cell behavior [8283], however, the orientation of many growth factors in single molecule level is not well controllable, which decreases the activity of the immobilized factors. In addition, immobilizing osteoinductive proteins on preferably osteoconductive matrices enables not only to control but even to prolong regenerative stimulation, thus minimizing side effects, while augmenting healing.…”
Section: Reviewmentioning
confidence: 99%